IMPROVING THE EFFECTIVENESS OF TEACHING THROUGH STEAM AND SMART METHODS IN TRAINING NATURAL AND SYNTHE FIBERS (Scientific journal of the Fergana State University, 2026)
The article provides several scientific grounds for the general concept of natural and artificial fibers and increasing these topics in teaching these topics in interactive methods. Threading efficiency through the use of these interactive methods was achieved by 20-30%